2016
DOI: 10.1111/josh.12433
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ethnicity in School‐Based Obesity Intervention for School‐Aged Children: A Pilot Evaluation

Abstract: The study demonstrates the intervention is effective, but that the effectiveness varies across ethnicity. Interventions can be made more efficient and cost-effective by targeting youth of a common ethnicity that has shown empirical responsiveness to certain program elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
(142 reference statements)
1
1
0
Order By: Relevance
“…The heterogeneity in terminology used to describe the study designs that we found is consistent with previous literature describing the diverse and ambiguous study design labels for nonrandomized intervention studies including cluster-allocated and population health studies (Reeves et al 2017). To bridge the differences in language 2017, Weiss et al (2015) No description 4 (17) (Bhave et al 2016;Bielec et al 2013;Karczewski et al 2016;Vinck et al 2016) Generalized estimation equations 2 (9) (Bolton et al 2017;Yang et al 2017) Difference-in-difference 2 (9) (Sadeghi et al 2017;Schwartz et al 2016) Analyzed graphically…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The heterogeneity in terminology used to describe the study designs that we found is consistent with previous literature describing the diverse and ambiguous study design labels for nonrandomized intervention studies including cluster-allocated and population health studies (Reeves et al 2017). To bridge the differences in language 2017, Weiss et al (2015) No description 4 (17) (Bhave et al 2016;Bielec et al 2013;Karczewski et al 2016;Vinck et al 2016) Generalized estimation equations 2 (9) (Bolton et al 2017;Yang et al 2017) Difference-in-difference 2 (9) (Sadeghi et al 2017;Schwartz et al 2016) Analyzed graphically…”
Section: Discussionsupporting
confidence: 62%
“…Distribution of study characteristics (n = 23) Characteristic Number of studies (%) Reference Statistical Analysis Method for group comparisons a GLM and/or ANOVA, ANCOVA, MANOVA 8 (35) Bielec et al(2013),Eichner et al (2016),Ermetici et al (2016),Reed et al (2013),Ronsley et al (2013),Treu et al (2017),Weiss et al (2015),Zhou et al (2014) Hierarchical multilevel or mixed effects regression models 7 (30)Karczewski et al (2016),Klakk et al (2013),Lazorick et al (2016),Mårild et al (2015),Sadeghi et al (2017),Swinburn et al (2014),Yang et al (2017) Linear or logistic regression models7 (30) Adab et al (2014), Bhave et al (2016), Bolton et al (2017), Economos et al (2013), Erfle and Gamble (2015), Schwartz et al (2016), Slusser et al Adab et al (2014), Bolton et al (2017), Erfle and Gamble (2015), Ermetici et al (2016), Karczewski et al (2016), Klakk et al (2013), Mårild et al (2015), Schwartz et al (2016), Slusser et al (2013), Swinburn et al (2014), Treu et al (2017), Weiss et al (2015), Yang et al (2017) Not conducted or no description 10 (48) Adab et al (2014), Bhave et al (2016), Erfle and Gamble (2015), Karczewski et al (2016), Reed et al (2013), Ronsley et al (2013), Vinck et al (2016), Weiss et al (2015), Yang et al (2017), Zhou et al (2014) Accounted for clustering effect in models 7 (33) Bolton et al (2017), Economos et al (2013), Lazorick et al (2016), Mårild et al (2015), Sadeghi et al (2017), Swinburn et al (2014), Treu et al Adab et al (2014), Bolton et al (2017), Economos et al (2013), Eichner et al (2016), Karczewski et al (2016), Klakk et al (2013), Lazorick et al (2016), Ronsley et al (2013), Slusser et al (2013), Swinburn et al (2014), Treu et al (2017), Vinck et al (2016), Yang et al (2017), Zhou et al (2014) Matched on demographic variables 8 (35) Adab et al (2014), Economos et al (2013), Ermetici et al (2016), Karczewski et al (2016), Klakk et al (2013), Weiss et al (2015), Yang et al (2017), Zhou et al Adab e...…”
mentioning
confidence: 99%